Development of Electroactive and Stable Current Collectors for Aqueous Batteries. Issue 5 (1st May 2022) - Bergman, Gil; Nimkar, Amey; Saha, Arka; Gavriel, Bar; Hen, Meital; Malchik, Fyodor; Fan, Tianju; Tsubery, Merav Nadav; Noked, Malachi; Sharon, Daniel; Shpigel, Netanel
Abstract : The need for low-cost, high-safety batteries for large-scale energy storage applications has sparked a surge in research of rechargeable aqueous batteries. While most research efforts are focused on the development of electrolyte formulations and electrode materials, it appears that the current collector impact on the battery performance is frequently overlooked. Even though the current collector is traditionally thought of as an inactive battery component, it is included in the battery energy density calculations, making its activation desirable. Furthermore, poor current collector selection can cause irreversible side reactions, resulting in rapid cell efficiency decay. Herein we propose a new approach to design current collectors that makes use of anodized Ti. The redox-active anodized Ti significantly improves the overall anode capacity and provides effective inhibition of hydrogen formation on the electrified interface. The use of TiO2 particles on an anodized Ti current collector in an aqueous electrolyte solution resulted in capacity of 130 mAh g −1 and exceptional capacity retention of 99% after 1000 cycles. Although the concept of active current collectors needs to be refined before it can be implemented in commercial cells, our findings indicate that this approach could be useful for improving overall cell performance without requiring significant changes to its configuration.